ChemInform Abstract: Gallium Analogue of Soluble Prussian Blue KGa[Fe(CN)6]·nH2O: Synthesis, Characterization, and Potential Biomedical Applications. Issue 21 (2nd May 2013) - Kandanapitiye, Murthi S.; Valley, Benjamin; Yang, Liu D.; Fry, Allyson M.; Woodward, Patrick M.; Huang, Songping D.
Abstract KGa[Fe(CN)6]·nH2O is synthesized by mixing equimolar aqueous solutions of Ga(NO3)3 and K4[Fe(CN)6].